Effect of Relative Humidity on Dose Response of Effervescent Glycine Pellet Dosimeters - Shinde, Santosh H (Journal of Science and Technology, 2013)
Glycine pellet dosimeter based on spectrophotometric read-out method has a useful dose range of 100 to 1000 Gy and is apt for routine dosimetry in low dose applications of radiation processing. The read-out method requires dissolution of these pellets in acidified solution of ferrous ammonium sulphate and xylenol orange, but due to appreciable hardness of these pellets it is required to stir the solution for complete dissolution which is generally not preferable. Hence fast dissolving pellets were fabricated using sodium bicarbonate as an effervescent agent. As sodium bicarbonate is hygroscopic, study of effect of relative humidity on dose response of these pellets was carried out in the present work.